Masyarakat 5.0 dalam Film AI Ho?kai karya Irie Yu - Santosa, Gitsali Hanum Salsabila; Damayanti, Silvia; Luhur Wedayanti, Ni Putu (Humanis, 2021)
This study aiming to analyze society 5.0, challenges and obstacles to realize society 5.0, and society 5.0 contribution to SDGs. The data was collected by using the documentation method and note-taking technique from the movie AI Houkai by Irie Yu. The data was analyzed descriptive qualitatively based on the theory of society 5.0 by Nakanishi, literature anthropology by Ratna, semiotics by Eco and  the  theory  of Young about  SDGs  theory. The finding shows that society 5.0 characterized as “Creative Society”of rapidly advancing innovation in digital technologies such as AI, the Internet of Things, robotics, and Augmented Reality. All people can share common goals. But, challenges and obstacles to realize such development time, permission from the government, and refusal from Japanese. Society 5.0 will contribute to delivering on SDGs.